Variations in economic growth across states in Malaysia: an exploratory analysis - Yusof, Yusniliyana; kalirajan, kaliappa (Emerald Insight, 2021)
The study contributes to the aim of regional development policy in reducing regional disparities, by examining the spatial balance in socioeconomic development across the states of Malaysia based on composite development index (CDI). Besides, the study has attempted to understand the issues in the development gaps across Malaysian states by evaluating the factors that explain the variation in economic growth Design/methodology/approach – This study uses three-stage least squares (3SLS) and bootstrap sampling and estimation techniques to examine the factors that explain the variations in the growth of development across the states in Malaysia. The analysis involves 13 states in Malaysia (Johor, Melaka, Negeri Sembilan, Pulau Pinang, Perak, Perlis, Selangor, Kedah, Kelantan, Pahang, Terengganu, Sabah and Sarawak) from 2005 to 2015